Psychosocial Aspect on Childhood Onset Psychosis - Carla R. Marchira (HM Publisher, 2020)
Introduction: Early-onset psychosis (EOP) or early-onset schizophrenia (EOS), also called childhood-onset schizophrenia (COS), is a rare and severe form of schizophrenia and is signed by psychotic symptoms by the age 12 years. The diagnosis criteria of COS are similar to the criteria for schizophrenia in adolescence and adulthood. The difference is that instead of showing deteriorating functioning, children may fail to achieve their level of social and academic functioning. This study aimed to report the psychosocial aspect of the COS case suffered by 12 years old girl treated for two years. Methods: In-depth interviews were conducted with patients with COS and parents about the course of illness, parent's acceptance, patient's perception, friends’ and teachers' acceptance, and patient's academic achievement. Results: Parents could accept the patient's illness with expectation and hope that patient could finish her education as high as possible through her medication. COS patient thinks that she has a